PENGARUH PENGGUNAAN JURNAL HARIAN SISWA TERHADAP PENINGKATAN PEMBIASAAN KARAKTER RELIGIUS DAN DISIPLIN - Dony Kurniawan (Universitas Negeri Surabaya, 2021)
ABSTRACT The study aims to knowing the effect of using studentsdaily journals on increasing character habituation religious and disciplinary. This research uses Quasi-Experimental Research. Sources of information in this study came from test results and observation. The subjects of this study were students of class VI SDN 1 Mlaya and SDN 2 Mlaya, Punggelan, Banjarnegara. The instruments in this study consisted of daily observation sheets and test sheets. This study uses quantitative data collection procedures. The data analysis method used is t-test and manova test. The result of this study is, 1) the use of students daily journals had a significant effect on the increase in the habituation of the religious character, 2) the use of students daily journals had a significant effect on the increase in habituation of the disciplines character, 3) the use students daily journals had a significant effect on increasing the habituation of religious character and disciplines. Keywords: daily journals, habituation of discipline and religious character ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan jurnal harian siswa terhadap peningkatan pembiasaan karakter religius dan disiplin. Jenis Penelitian ini adalah Quasi-Experimental Research. Sumber informasi berasal dari data primer yaitu hasil tes dan data sekunder yaitu hasil observasi. Subyek penelitian ini adalah siswa kelas VI SDN 1 Mlaya dan SDN 2 Mlaya, Kecamatan Punggelan, Kabupaten Banjarnegara. Instrumen penelitian ini terdiri dari lembar observasi harian dan lembar tes. Penelitian ini menggunakan prosedur pengumpulan data kuantitatif. Metode analisis data yang digunakan yaitu analisis deskriptif dan analisis inferensial menggunakan uji-t dan uji Manova. Hasil penelitian ini yaitu, 1) penggunaan jurnal harian siswa berpengaruh signifikan terhadap peningkatan pembiasaan karakter religius, 2) penggunaan jurnal harian siswa berpengaruh signifikan terhadap peningkatan pembiasaan karakter disiplin, 3) Penggunaan jurnal harian siswa berpengaruh signifikan terhadap peningkatan pembiasaan karakter religius dan disiplin secara simultan. Kata Kunci:Jurnal harian, pembiasaan karakter religius dan disiplin